Harnessing gravity-driven membranes in activated sludge bioreactors: Enhancing energy efficiency and mitigating biofouling via quorum quenching - Jun-U Jang; Jeongmi Park; Hyunjung Kim; Seonki Lee; Kwang-Ho Choo; Kibaek Lee (npj Clean Water)
Abstract This study developed a gravity-driven membrane bioreactor (GD-MBR) to reduce energy consumption in wastewater treatment. The system maintained a stable flux of 6 L/m2/h when treating high-organic wastewater loads (TOC: 270 mg/L, SS: 7,000 mg/L), surpassing conventional GDMs (2–4 L/m²/h). Quorum quenching (QQ) extended stable flux duration and increased cumulative permeate volume by 26%, treating 130 L and 73 L over 65 and 35 days, respectively, compared to 105 L and 50 L in the non-QQ system. QQ reduced biofilm extracellular polymeric substances (polysaccharides by 30% and proteins by 20%) and significantly lowered N-acylhomoserine lactone concentrations (e.g., C8-HSL: 0.02 ± 0.01 pM vs. 0.34 ± 0.03 pM after 106 days). Next-generation sequencing showed increased microbial network complexity (edges: 32 vs. 27) and downregulation of biofilm- and quorum-sensing-related genes (HigA-1, Fis, LuxR family). These results highlight the potential of QQ-enhanced GD-MBRs for energy-efficient treatment of high-organic wastewater loads.